PERAN INFORMASI AKUNTANSI SEBAGAI ALAT AKUNTABILITAS INTERNAL, EVALUASI KINERJA KEUANGAN DAN PENGAMBILAN KEPUTUSAN KEUANGAN PADA INSTANSI VERTIKAL PEMERINTAH PUSAT - Wakhid Susilo (Master in Accounting Program, 2014)
The purpose of this study was to examine the influence of the quality of accounting information to internal accountability, the evaluation of financial performance, and financial decision making in the vertical agencies of central government. In further, this study also to determine the cause of the quality of accounting information wasnot so ideal and accounting information has not been used optimally. In addition, the study was detected the cause accounting information has not been used optimally when in the preparation of financial statements requires sources of funds, energy, thoughts, time in large numbers. The sample in this research is a vertical agencies in the city of Yogyakarta, Sleman and Bantul. This study used mixed methods that is a combination of the quantitative methods and qualitative methods with sequential explanatory strategy. Quantitative and qualitative data analysis showed similar results that the accounting information has not been used optimally. Development theory and interpretation of this study were drawn from Mardiasmo opinion, the Government Accounting Standards, and Institutional Isomorphism.